2019
DOI: 10.1016/j.bja.2018.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational cohort study of the association between antiplatelet therapy, bleeding and thrombosis in patients with coronary stents undergoing noncardiac surgery

Abstract: Background: The perioperative management of antiplatelet therapy in noncardiac surgery patients who have undergone previous percutaneous coronary intervention (PCI) remains a dilemma. Continuing dual antiplatelet therapy (DAPT) may carry a risk of bleeding, while stopping antiplatelet therapy may increase the risk of perioperative major adverse cardiovascular events (MACE). Methods: Occurrence of Bleeding and Thrombosis during Antiplatelet Therapy In Non-Cardiac Surgery (OBTAIN) was an international prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…The maintenance of aspirin or clopidogrel until surgery was not found to be significantly associated with MACCE in our results, which does not agree with the previous guidelines [26]. However, the protective role of an antiplatelet agent against the major adverse cardiovascular event was reported to be insignificant by a recent prospective observational study [44]. Another recent retrospective study of patients with second-generation DES reported that the incidence of major adverse cardiac events was not influenced by antiplatelet therapy [45].…”
Section: Discussioncontrasting
confidence: 89%
“…The maintenance of aspirin or clopidogrel until surgery was not found to be significantly associated with MACCE in our results, which does not agree with the previous guidelines [26]. However, the protective role of an antiplatelet agent against the major adverse cardiovascular event was reported to be insignificant by a recent prospective observational study [44]. Another recent retrospective study of patients with second-generation DES reported that the incidence of major adverse cardiac events was not influenced by antiplatelet therapy [45].…”
Section: Discussioncontrasting
confidence: 89%
“…Those results tended to persist when patients who continued dual APT (DAPT) were excluded from the analysis, suggesting that the risk of MACE is also linked to discontinuation of aspirin monotherapy. However, the results by Hong and colleagues 2 discontinuation of APT for <7 days in their study did not lead to adverse outcomes. Even after taking note of these limitations, this study does highlight the dilemma of routine protracted discontinuation of APT.…”
mentioning
confidence: 77%
“…EditordWe are grateful to Karim and colleagues 1 for their thoughtful comments on the Occurrence of Bleeding and Thrombosis during Antiplatelet therapy in Noncardiac surgery (OBTAIN) study. 2 They expressed concern that the results of OBTAIN might be used to advocate the discontinuation of dual antiplatelet therapy (DAPT) in all patients who have undergone percutaneous coronary intervention (PCI) and now require noncardiac surgery. We agree that this clinical problem requires a nuanced approach.…”
mentioning
confidence: 99%
“…1 In this context, Howell et al, conducted the OBTAIN multicentre prospective cohort study to better delineate the risks and benefits of continuing or interrupting DAPT in patients undergoing non-cardiac surgery after PCI within the 4 yrs preceding the index non-cardiac surgery. 8 identified as part of routine care included cardiac (myocardial infarction or PCI for cardiac event) and bleeding (reoperation for bleeding, gastrointestinal or intracranial haemorrhage, and spinal or epidural haematoma) events. Importantly, there was no standardised postoperative surveillance (i.e.…”
mentioning
confidence: 99%